Non-C282Y familial iron overload: evidence for locus heterogeneity in haemochromatosis. Issue 11 (November 1998) - Pinson, S; Yaouanq, J; Jouanolle, A M; Turlin, B; Plauchu, H
Abstract : Haemochromatosis (HC) is an autosomal recessive disease with progressive iron overload leading to midlife onset of clinical complications. The causal gene (HFE) maps to 6p, in close linkage with the HLA class I genes. An HFE candidate gene recently identified has two missense mutations (C282Y and H63D) associated with the disease. Here we document the phenotypic and genetic analysis of a nuclear family comprising two sibs with symptomatic and massive iron overload before the age of 25. The disease seemed to be recessively transmitted and fitted the agreed criteria for haemochromatosis, but was neither associated with the C282Y and H63D mutations nor linked with HLA markers. Our data strongly support locus heterogeneity in haemochromatosis by showing evidence that the gene responsible for juvenile haemochromatosis (JH) does not map to 6p. In the absence of clear cut phenotypic distinction from typical haemochromatosis, patients below 30 years of age and C282Y negative should be considered as putative juvenile cases. This has practical implications in genetic counselling and family management.